Painting Music in the Sixteenth Century: Essays in Iconography - Slim, H. Colin (Aldershot Ashgate, 2002)
This text examines the role that music can play in the artworks of the Renaissance, in particular, Italian painting of the 16th century. Art historians sometimes neglect the role of music and, especially, that of musical notation when studying works of art. This study identifies musical compositions wholly or partly inscribed in paintings, tapestries, ceramics and prints, and seeks reasons why these particualr muscial compositions were included, analyzing their relevance to the scenes depicted. The author aims to demonstrate that identifying a musical composition, especially if it has a text, leads to the formation of ideas about iconographical functions and thus augments interpretations of the artwork.